Urokinase receptor and CXCR4 are regulated by common microRNAs in leukaemia cells - Alfano, Daniela (J Cell Mol Med, 2015)
The urokinase-type plasminogen activator (uPA) receptor (uPAR) focuses uPA proteolytic activity on the cell membrane, promoting localized degradation of extracellular matrix (ECM), and binds vitronectin (VN), mediating cell adhesion to the ECM. uPAR-bound uPA and VN induce proteolysis-independent intracellular signalling, regulating cell adhesion, migration, survival and proliferation. uPAR cross-talks with CXCR4, the receptor for the stroma-derived factor 1 chemokine. CXCR4 is crucial in the trafficking of hematopoietic stem cells from/to the bone marrow, which involves also uPAR. Both uPAR and CXCR4 are expressed in acute myeloid leukaemia (AML), with a lower expression in undifferentiated and myeloid subsets, and higher expression in myelomonocytic and promyelocytic subsets. We hypothesized a microRNA (miR)-mediated co-regulation of uPAR and CXCR4 expression, which could allow their cross-talk at the cell surface. We identified three miRs, miR-146a, miR-335 and miR-622, regulating the expression of both uPAR and CXCR4 in AML cell lines. Indeed, these miRs directly target the 3′untranslated region of both uPAR- and CXCR4-mRNAs; accordingly, uPAR/CXCR4 expression is reduced by their overexpression in AML cells and increased by their specific inhibitors. Overexpression of all three miRs impairs migration, invasion and proliferation of myelomonocytic cells. Interestingly, we observed an inverse relationship between uPAR/CXCR4 expression and miR-146a and miR-335 levels in AML blasts, suggesting their possible role in the regulation of uPAR/CXCR4 expression also in vivo.